ارشاد احمد صدیقی کے افسانوی مجموعہ "دوسری خدائی" کا موضوعاتی مطالعہ (Al-Aasar, 2025)
Irshad Ahmad Siddiqui’s The Other God is a compelling collection of short stories that delves into the intricate tapestry of human experience. Through a blend of reality and fiction, Siddiqui explores profound themes such as love, loss, and the search for meaning. Each story offers a unique perspective, inviting readers to contemplate the complexities of human psychology and the internal struggles that shape our lives. Siddiqui’s writing style is both simple and profound, drawing readers into the lives of his characters and encouraging empathy Whether exploring the quiet desperation of everyday life or the fantastical realms of the imagination, The Other God is a thought-provoking and emotionally resonant read.